Pasting and reversing operations over some rings (2010)
This paper examines two operations, pasting and reversing, defined as a natural mappings over some rings, such as polynomials and linear dierential operators, which is a dierential ring. We obtain some properties of these operations over these rings. This result allows us to establish some properties of natural numbers appearing in recreational mathematics.